Implementation of Teaching Assistance on Mathematics and Natural Sciences Olympiad in Elementary School - Deta, Utama Alan; Lintangesukamanjaya, Rahmatta Thoriq; Shinta, Chamila El; Mustafaroh, Vinka Amalia; Putri, Natasya Safira; Alemgadmi, Khaled Issa Khalifa (Mitra Edukasi dan Publikasi, 2023)
The Mathematics and Natural Sciences (MIPA) Olympiad for Elementary School (SD/MI Equivalents) in Tuban Regency, which was organized by Unesa students community services (KKN) and supervised by the Tuban Education Office, is a competition activity that is engaged in the world of education. This Olympic activity was held for 3 days starting from the technical meeting stage, preliminary session and final. Activities carried out with the aim of improving the quality of education and student resources in mastering mathematics and natural sciences are carried out at the Prunggahan Wetan Village Hall and zoom meetings. The results of the MIPA Olympiad were able to produce five categories of winners, namely Champion 1, 2, 3, hope 1 and hope 2. The event was enlivened by the appearance of Unesa KKN students and attended directly by the Head of the Middle School Office of Tuban Education. It is hoped that with this competition, with the form of competition, it is hoped that the new generation will be able to maximize their potential and also advance their scientific spirit so that they can compete with global challenges in the future.